Understanding religious conversion - Rambo, Lewis R. (Lewis Ray), 1943- (New Haven : Yale University, 1993)
Looking at a wide variety of religions, this work offers an exploration of religious conversion. The phenomena is approached from a variety of disciplines, including psychology, sociology, theology and anthropology.
Models and methods -- Context -- Crisis -- Quest -- The advocate -- The advocate's strategy -- Encounter between advocate and convert -- Interaction -- Commitment -- Consequences.
Includes bibliographical references (pages 209-234) and index.
English.
Description based on online resource; title from digital title page (viewed on March 02, 2023).
JSTOR
Keywords: Conversion; Psychology and religion; Religion and Psychology; Conversion; Psychologie et religion; RELIGION -- Spirituality; RELIGION -- General; Psychology and religion; Conversion; Konversion; Bekering; Conversão religiosa; Religião.; Christianity -- Religious experiences -- Conversion